2013
DOI: 10.1186/1471-2407-13-349
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of YAP 1 contributes to progressive features and poor prognosis of human urothelial carcinoma of the bladder

Abstract: BackgroundYes-associated protein 1 (YAP 1), the nuclear effector of the Hippo pathway, is a key regulator of organ size and a candidate human oncogene in multiple tumors. However, the expression dynamics of YAP 1 in urothelial carcinoma of the bladder (UCB) and its clinical/prognostic significance are unclear.MethodsIn this study, the methods of quantitative real-time polymerase chain reaction (qRT-PCR), Western blotting and immunohistochemistry (IHC) were utilized to investigate mRNA/ protein expression of YA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 29 publications
4
94
0
Order By: Relevance
“…We observed a decrease of YAP1 and pYAP1 in BCA tissue compared to normal urothelial tissue. During the later courses of our study, Liu et al [18] reported an increase of YAP1 mRNA and protein levels in BCA compared to normal urothelial tissue; furthermore, the expression of YAP1 was predominantly increased in the nucleus. Furthermore, YAP1 expression was correlated with advanced tumor stage and patients survival.…”
Section: Discussionsupporting
confidence: 55%
“…We observed a decrease of YAP1 and pYAP1 in BCA tissue compared to normal urothelial tissue. During the later courses of our study, Liu et al [18] reported an increase of YAP1 mRNA and protein levels in BCA compared to normal urothelial tissue; furthermore, the expression of YAP1 was predominantly increased in the nucleus. Furthermore, YAP1 expression was correlated with advanced tumor stage and patients survival.…”
Section: Discussionsupporting
confidence: 55%
“…Tissues and cells were lysed and analyzed by western blotting as described [5] with the following antibodies: rabbit polyclonal anti-YAP1 (1:1,500, ABclonal, MA) and mouse monoclonal anti-β-actin (1:2,000, Sigma). Horseradish peroxidase-conjugated secondary antibodies were acquired from Cell Signaling Technology (1:2,000, CST, MA).…”
Section: Western Blottingmentioning
confidence: 99%
“…Immunohistochemical staining was conducted on formalinfixed paraffin-embedded blocks, as described previously [5].…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of YAP1 protein correlate with cancer progression, and poor prognosis for the bladder, prostate, ovarian and uterine cancer patients [8][9][10][11][12]. In turn, irradiation induced apoptosis of prostate cancer cells has been linked to a decrease in the levels of the YAP1 protein and a consequent raise in the BAX cell death factor [12].…”
Section: Planar Polarity Factors As Potential Tumor Suppressors In Thmentioning
confidence: 99%